The Socio-Economic Condition of the Fish Papalele Group in Nuwewang Village, Letti Subdistrict, Maluku Barat Daya Regency - Reindino Letedara; Wiclif Sephnath Pinoa; Dwi Partini (Jurnal Pendidikan Geografi Unpatti, 2024)
This research examines the social and economic conditions of the Papalele fish group in Nuwewang Village, Letti Sub-district, Southwest Maluku Regency, focusing on access to capital, opportunities, and constraints faced in running their business. Through the narrative analysis method, this study found that Papalele groups rely on flexible payment systems with fishermen, but face limited access to formal financial institutions and a lack of financial management knowledge. While there are opportunities to increase income through product diversification and cooperation with wider markets, fluctuating fish prices and other social constraints pose significant challenges. Significant challenges. The results of this study indicate the need for support from the government and community to improve the capacity and sustainability of Papalele groups' businesses in the future.